Analisis Efektivitas Pemungutan Retribusi Daerah Atas Pengujian Kendaraan Bermotor Kedaung Angke Tahun 2023 - Fiatri, Lisa Arisa (Institut Ilmu Sosial dan Manajemen STIAMI, 2023)
The purpose of this study is to evaluate the effectiveness of local retaliatory collection of motor vehicle testing in Kedaung Angke. The research uses a qualitative approach with a descriptive method. Research results show that the share of vehicle taxes in the collection of utility taxes was only 13.3% on average in 2020-2022 . According to the theory of effectiveness, the implies that the collection process is not efficient. Several challenges may be contributing to this ineffectiveness, including levels of public compliance, enforcement of regulations, limitations in infrastructure and technology, maintenance and service quality, the impact of the pandemic or emergency situations, and the importance of effective supervision and audits. To address these challenges in the collection of Local Retributions at the Vehicle Testing Management Unit (UPPKB) in Kedaung Angke, several solutions are proposed, including public awareness campaigns and education, infrastructureand technology enhancements, transparency in the retribution collection process, improved service quality, flexible payment options, rigorous supervision and auditing, partnerships with the private sector, and adaptability during pandemic or emergency situations.